2017
DOI: 10.1016/j.jtcvs.2016.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing cardiac arrest in children undergoing cardiac surgery: A single-center study

Abstract: This single-center study demonstrates that characterizing cardiac arrest in children undergoing cardiac surgery using definitions from 2 societies helps to increase data granularity and understand the relationship between cardiac arrest and heart operation in a better way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 18 publications
2
15
0
1
Order By: Relevance
“…Longer duration of arrest has been associated with decreased survival after both paediatric in-hospital and out-of-hospital arrest. 3, 6, 9, 17, 24, 28 Our findings also show an adrenaline dosing interval of 3 to <5 minutes results in greater 12-month survival than more or less frequent dosing. These findings support current American Heart Association (AHA) guidelines that recommend adrenaline administration at intervals of 3–5 minutes during resuscitation.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Longer duration of arrest has been associated with decreased survival after both paediatric in-hospital and out-of-hospital arrest. 3, 6, 9, 17, 24, 28 Our findings also show an adrenaline dosing interval of 3 to <5 minutes results in greater 12-month survival than more or less frequent dosing. These findings support current American Heart Association (AHA) guidelines that recommend adrenaline administration at intervals of 3–5 minutes during resuscitation.…”
Section: Discussionsupporting
confidence: 63%
“…4 Incidence rates are estimated at 1% to 3% for children in paediatric ICU 68 and 3% to 6% in cardiac ICU. 911 Epidemiologic studies of paediatric in-hospital cardiac arrest are primarily based on registries with voluntary reporting of data, or are retrospective single institution studies. 45, 711 Outcomes have generally been limited to mortality at hospital discharge and functional status among survivors using subjective measures such as the Paediatric Cerebral Performance Category (PCPC) scale.…”
Section: Introductionmentioning
confidence: 99%
“…In-hospital-cardiac-arrest (IHCA) occurs in 3% to 4% of children recovering from cardiac surgery with an associated mortality of 35% to 40%; a high proportion of survivors experience long-term neurodevelopmental disability. 1,2 Understanding patterns of IHCA timing and its association with outcome can potentially lead to the development of risk stratification tools and targeted management protocols. Currently there are no reports linking timing of IHCA after pediatric cardiac surgery and outcome.…”
mentioning
confidence: 99%
“…11,24 A life threatening complication impacting brain oxygenation and therefore development is cardiac arrest with subsequent cardiopulmonary resuscitation, which occurs in approximately 4.5% of children with CHD before or after cardiac surgery. 25 In surviving patients, pronounced neurological deficits are frequently observed and are associated with serum biomarkers such as neuron-specific enolase or the S100ß protein, as well as duration of cardiopulmonary resuscitation. 26,27 Importantly, most studies investigating the development of children with CHD and/or after cardiopulmonary resuscitation are cross-sectional and only a few studies have observed the longitudinal development of these children longitudinally during the first years of life.…”
mentioning
confidence: 99%